A Dosimetric Comparison of Volumetric Modulated Arc Therapy and Intensity Modulated Radiotherapy in Patients Treated with Post-Mastectomy Radiotherapy - Samuel Adeneye; Michael Akpochafor; Nusirat Adedewe; Muhammad Habeebu; Ramotallah Jubril; Abe Adebayo; Omolola Salako; Adedayo Joseph; Inioluwa Ariyo; Eseoghene Awhariado; Rasak Lawal (European Journal of Breast Health, 2023)

(untitled)
Objective:Radiotherapy continues to play an important role in the management of breast cancer. This study compared the dosimetric differences between the techniques of intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) in breast cancer patients who had radiotherapy after mastectomy.Materials and Methods:Forty post-mastectomy patients (19 right-sided breast and 21 left-sided breast) treated with the IMRT technique using 7-9 fields who were re-planned with VMAT using 2 coplanar arc on the Varian Vital beam linear accelerator between January, 2020 and August, 2021 were included in this study. The patients received 42 Gy in 15 fractions to the chest wall, lymph nodes and supraclavicular nodes. The dosimetric parameter for planning target volume (PTV), organs at risk (OAR) and the integral dose to the body were analysed. Student’s t-test for two independent means was used to analyse the dosimetric differences between the plans.Results:Clinical goals were achieved for both techniques. In terms of PTV coverage at 95% (IMRT: 712.17±233) vs (VMAT: 694.9±214) and the homogeneity index (IMRT: 0.075±0.04) vs (VMAT: 0.104±0.03), IMRT resulted in better dose coverage and homogeneity than VMAT. However, with the conformity index, no significant difference was seen. As regards the OARs, the mean doses, V5, V10, V20, V30, and V40 for the Ipsilateral-lung were lower in IMRT plans than in VMAT plans with a non-significant variation (p-values = 0.141, 0.416, 0.954, 0.443, and 1 respectively). Regarding the mean dose to the heart, low-dose volumes V5, V10, and high-dose volume V30 were significantly reduced in IMRT compared to VMAT. When comparing the dose to the contralateral breast, IMRT achieved a significantly lower mean dose than VMAT (2.9 vs 3.62, p = 0.0148). For MU, VMAT showed lower MU compared to IMRT with a non-significant difference.Conclusion:With IMRT, better PTV coverage, homogeneity and OAR sparing were observed. Additionally, VMAT resulted in a lower delivery time than IMRT. Overall, both techniques offered dosimetric qualities that were clinically acceptable.